2018
DOI: 10.7150/thno.22182
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer-associated Fibroblast-derived IL-6 Promotes Head and Neck Cancer Progression via the Osteopontin-NF-kappa B Signaling Pathway

Abstract: Osteopontin (OPN), a chemokine-like protein, plays a crucial role in the proliferation and metastasis of various cancers. However, how tumor stroma modulates the expression of neoplastic OPN and the multifaceted roles of OPN in head and neck cancer (HNC) are unclear. In this study, we tried to investigate the bridging role of OPN between tumor stroma and cancer cells.Methods: Immunohistochemical staining and quantitative real-time PCR were used to detect OPN expression in HNC tissues, and the correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 63 publications
2
102
0
Order By: Relevance
“…Furthermore, the JAK/STAT3 pathway, the IL-6 downstream target (47,48), was downregulated in ATF3-overexpressing HDFs. IL-6 has been shown to play a promoting role in the pathogenesis and development of malignancies in many kinds of tumors, including melanoma, and was also shown to be highly expressed by CAFs contacting different tumor types (34,(49)(50)(51). Therefore, we could conclude that the inhibitory effect of ATF3-overexpressing HDFs on melanoma cell growth and migration is mainly through the IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the JAK/STAT3 pathway, the IL-6 downstream target (47,48), was downregulated in ATF3-overexpressing HDFs. IL-6 has been shown to play a promoting role in the pathogenesis and development of malignancies in many kinds of tumors, including melanoma, and was also shown to be highly expressed by CAFs contacting different tumor types (34,(49)(50)(51). Therefore, we could conclude that the inhibitory effect of ATF3-overexpressing HDFs on melanoma cell growth and migration is mainly through the IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 86%
“…Mounting evidence suggests that the NF-κB signaling pathway is involved in the progression of various human tumors, including those of ovarian cancer (43), prostate cancer (44), cervical cancer (45), as well as head and neck cancer (46). A recent study demonstrated that TRIM22 negatively regulates the tumor necrosis factor receptor-associated factor 6 (TRAF6)-stimulated NF-κB pathway by binding to the TRIM22 N-terminal RING domain (47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these possible fibroblast activation models by C2 cells, our data further revealed a potential mechanism for reciprocal fibroblast–tumour cell communication. Studies have shown a proproliferative effect of IL‐6 on CAFs and have correlated its expression with increased levels of the CAF marker ACTA2 [55,56]. However, IL‐6 is also an important mediator of a dynamic tumour cell–CAF crosstalk by not only promoting fibroblast activation, but also supporting tumour cell growth in humans [57].…”
Section: Discussionmentioning
confidence: 99%